Sosisalisasi Rehabilitasi Hutan Bakau Dalam Penyelamatan Lingkungan Pesisir Desa Buruk Bakul Kecamatan Bukit Batu, Bengkalis - Yusni Ikhwan Siregar; Defri Yoza; Efriyeldi Efriyeldi (CANANG: Jurnal Pengabdian Masyarakat, 2021)
Degaradation and destruction rate of the coastal ecosystem, especially mangrove ecosystem, increase in Bengkalis Regency due to over exploitation and conversion. Therefore attempts to overcome the problem become important. The objective of the study was to provide and promote basic knowledge on the importance of mangrove ecosystem to the environment, especially to the village community of Buruk Bakul. Further, the extension also aimed at providing physical, ecological and economical use and benefit that people obtain from the mangrove ecosystem. The participants of total 30 persons, with background of farmer, fishermen, local leader, young leader, and of non-government organization “Sekat Bakau” of the Buruk Bakul were trained.  Pre-survey were done to find out the main issue on coastal environmental threats in the village area. The extension were carried out through class presentation, interactive discussion and demonstration of mangrove plantation in the field. The effectiveness of the extension were evaluated to the participants through items in questioner which evaluate the change in knowledge and understanding on the ecological, economical and physical function of mangrove ecosystem.  Apparently, the level of knowledge were categorize into very good (60%),good (30%) and fair (10%). Based on that, the extension were categorized success.. The impact on the implementation in the field were that of knowledge dissemination to young group in technical nursery and planting of mangrove trees.